Numerical Analysis Spectral Huygens Filter for pulsed broadband Terahertz Radiation. (December 2019) - Liu, X; Petrov, N V; Kulya, M S; Tsypkin, A N; Grachev, Ya V; Kozlov, S A
Abstract: In this paper, we consider a Huygens filter for a specified frequency lying within a broad spectrum of a pulsed THz radiation which represents simplest two-zone plate. The condition of the infinite plane wave and the Gaussian beam are separately used as the initial source has been discussed. A property method of terahertz spectral filter has been explored.